Modern Pondok Pesantren: Maintaining Tradition in Modern System - Hamid Fahmy Zarkasyi (TSAQAFAH, 2015)
Pondok pesantren is a renown Islamic education system that generally categorized as traditional system. However, there were tendencies of certain pondok pesantren that developed their system from traditional into modern system of education. Here, it may be classified that pondok pesantren have two systems of education: traditional and modern. Traditional pesantren, tend to implement the curriculum based on certain classical books called kitab kuning while maintaining unique traditional method of instruction such as sorogan, bandongan, halaqah, and mudhakarah. In the other hand, modern pesantren have their the curriculum modified in order to be fitted with school curriculum emphasizing the subject of Islamic studies and employing full modern method of instruction. It is attractively to known then, that it there were tendencies of certain pondok pesantren that developed their system from traditional into modern system of education. By this development a new model of pondok pesantren emerged that characteristically can be identified as an Islamic education system using modern system Curriculum, applying modern system and methodology of instruction and employing modern institutional system, yet it maintain traditional value system for their daily life in the campus. The writer found in this research that modern system of pesantren initiated with Wahid Hasyim and Jamiah Khair, then ultimately on the hand of Imam Zarkasyi. This paper will try to elaborate history of pesantren in Indonesia, improved later several aspects of modernization of pesantren system.